2018
DOI: 10.1002/jcla.22600
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of the mindray anti‐HCV assay for the detection of hepatitis C virus infection

Abstract: The Mindray anti-HCV assay displays a similar sensitivity to the Elecsys anti-HCV II assay with respect to the early detection of HCV infection. The Mindray anti-HCV assay shows excellent diagnostic performance and is suitable for the screening of HCV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…ChIVD LiCA anti‐HCV assay showed a high sensitivity of 96.39% and excellent specificity of 99.95%, PPV of 89.58%, and NPV of 99.97%, which were superior to those of the Architect anti‐HCV assay. And the diagnostic performance of ChIVD LiCA anti‐HCV assay was similar to that of Elecsys reported in other studies …”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…ChIVD LiCA anti‐HCV assay showed a high sensitivity of 96.39% and excellent specificity of 99.95%, PPV of 89.58%, and NPV of 99.97%, which were superior to those of the Architect anti‐HCV assay. And the diagnostic performance of ChIVD LiCA anti‐HCV assay was similar to that of Elecsys reported in other studies …”
Section: Discussionsupporting
confidence: 84%
“…As the screening method, chemiluminescence and electrochemiluminescence immunoassays for HCV antibody (the antibodies of HCV core, NS3‐4, and NS5 proteins) have been widely used to diagnose HCV infection in clinical laboratories. Previous studies have compared the diagnostic performance of different methods and revealed that the false positive rates of these assays are relatively high . Also, these methods for anti‐HCV detection require several washing steps so that the detection speed is limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation